Magnetic excitations in square lattice 2D Heisenberg Antiferromagnet Sr3Fe2O6.5 - Dr Anil Jain; Dr Devashi Adroja; Professor Bernhard Keimer (ISIS Facility, 2019)
Strontium iron oxides belonging to the RP series Srn+1FenO3n+1 (n = 1, 2, ..,1) may offer unique insights into the differences between the magnetic properties of the manganates,ruthenates, and ferrates. The present proposal on Sr3Fe2O6.5 is motivated by our recent observations that there is a change in crystal structure from tetragonal (for Sr3Fe2O7) to orthorhombic ( for Sr3Fe2O6.5), where the 4-fold symmetry is lost. A preliminary refinement suggests that in the magnetic structure moments lie perpendicular to the c axis and are coupled ferromagnetically within each bilayer. Upon heating to 335 K, the crystal structure changes to tetragonal and the compound doesn't order magnetically after cooling down to 2 K (cooling from 335 K,called quenched condition). We want to investigation the magnetic excitation in the quenched condition using the chopper spectrometer, MERLIN. ISIS, U.K
Keywords: STFC ISIS Neutron and Muon Data